Comparative Efficacy of CO2 and Ozone Gases Against Ephestia cautella (Lepidoptera: Pyralidae) Larvae Under Different Temperature Regimes. Issue 1 (10th September 2015) - Husain, M.; Rasool, Khawaja G.; Tufail, Muhammad; Alhamdan, Abdullah M. A.; Mehmood, Khalid; Aldawood, Abdulrahman S.
Abstract : Comparative efficacy of three different modified atmospheres: 100% CO2, 75% CO2 + 25% N2, and 22 ppm ozone were examined against larval mortality of the almond moth, Ephestia cautella (Walker) (Lepidoptera: Pyralidae) at temperature regimes of 25°C and 35 ± 2°C and 60 ± 5% relative humidity, and 9:15 dark and light. Wandering young larval instars, which are fast growing, large enough in size and considered as more tolerant to modified atmosphere, were collected directly from the rearing culture, placed inside pitted date fruits of vars.: "Khudri, " "Ruziz, " and "Saqie, " were treated with aforementioned gases for 24, 48, and 72 h. The immediate and delayed larval mortality was recorded after each exposure timing. Ozone possessed the strongest fumigant toxicity causing 100% mortality with all varieties, at 25 and 35°C after 24 h exposure and was more effective than 75% CO2 that caused 83 and 100% immediate mortality with variety ruziz at 25 and 35°C, respectively. Extending the treatments exposure time to 72 h, 100% mortality was recorded by exposing larvae to any of the studied gases at 25 and 35°C. These results suggest that gases and temperature used in this study can be effectively used to control E. cautella in dates and stored grains.